Analisis Model Propagasi 3GPP TR38.900 Untuk Perencanaan Jaringan 5G New Radio (NR) Pada Frekuensi 2300 MHz di Area Urban - Yuliana, Hajiar; Santoso, Fajar Malik; Basuki, Sofyan; Hidayat, Muhammad Reza (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2022)
5G New Radio (NR) services can provide high data rates and low latency. The existence of 5G technology, especially in Indonesia, has been implemented by several cellular operators in the 2300 MHz and 1800 MHz frequencies. Therefore, a more detailed planning analysis is needed, especially in urban areas. In this study, planning for the 5G network needed in one of the urban areas in Cimahi City, West Java. This research was carried out for a frequency of 2300 MHz using the coverage planning analysis method. The propagation model used in this study is 3GPP TR38.900. Based on the analysis and calculations performed, obtained 26 sites for the area of ​​Cimahi City which has an area of ​​about 40.3 km². The location of the site is arranged based on the coverage conditions in the area and also based on the distribution of the 4G network that previously existed in the area, because the 5G planning used is the Non-Standalone 5G type. Based on the results of the coverage analysis carried out, the condition of the Synchronization Signal Reference Signal Received Power (SS-RSRP) signal level above -90 dBm reached 27.3% of the total area. This shows that the 5G network planning in this area can only cover an area of ​​up to a quarter of the total area.